Revisiting the Okayama model of education for sustainable development by using the quintuple helix model of analysis’ - Zen, Irina Safitri (2019)
The Japanese education for sustainable development, ESD movement has sought to collectively challenge conventional education in the context of education for sustainability. As a community-based activity led by citizens, the Okayama ESD project grows up to 260 establishments of community learning centers, CLCs or kominkans in implementing ESD in Okayama prefecture. The CLCs works closely with the school district and become the ESD hub for the school and some of kominkan become sources for the online lifelong learning center. In Okayama City, it is reported that more than ten percent of the population is involved in activities for making sustainable livelihood; where about 30,000 people are engaged in the sector of environmental protection, about 34,000 in the sector of promotion of gender equality, and about 7000 in the health promotion sector and many more. Concerning global environmental challenges, there are six thematic issues highlighted in the Okayama Commitments, namely: environmental conservation, disaster risk reduction (DRR), income generation, entrepreneurship, community development, cultural diversity and dialogue, intergenerational exchange, literacy, and empowerment.